2020
DOI: 10.1016/j.brs.2020.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative changes in the H-reflex pathway during deep brain stimulation surgery for Parkinson’s disease: A potential biomarker for optimal electrode placement

Abstract: Background: Deep Brain Stimulation (DBS) targeting the subthalamic nucleus (STN) and globus pallidus interna (GPi) is an effective treatment for cardinal motor symptoms and motor complications in Parkinson's Disease (PD). However, malpositioned DBS electrodes can result in suboptimal therapeutic response. Objective: We explored whether recovery of the H-reflexdan easily measured electrophysiological analogue of the stretch reflex, known to be altered in PDdcould serve as an adjunct biomarker of suboptimal vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…This is supported by several other studies that found that STN-DBS alters postural alignment and consequently can effect postural reflex responses [ 71 , 76 , 105 ]. Studies investigating the latency of electrically induced so-called Hofmann (H) reflex, which is an analogue of the mechanically induced stretch reflex, also provide evidence that STN-DBS may change reflex timing [ 156 , 157 , 158 ]. Pötter-Nerger et al reported the facilitation effects of the H-reflex after STN-DBS was switched on [ 156 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by several other studies that found that STN-DBS alters postural alignment and consequently can effect postural reflex responses [ 71 , 76 , 105 ]. Studies investigating the latency of electrically induced so-called Hofmann (H) reflex, which is an analogue of the mechanically induced stretch reflex, also provide evidence that STN-DBS may change reflex timing [ 156 , 157 , 158 ]. Pötter-Nerger et al reported the facilitation effects of the H-reflex after STN-DBS was switched on [ 156 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the electrophysiological studies on PD patients undergoing deep brain stimulation (DBS) surgery showed significant improvement in PSI soon after the therapy (Pierantozzi et al 2008;Andrews et al 2020). Combining these study results (Morita et al 2000;Pierantozzi et al 2008;Silva-Batista et al 2017;Andrews et al 2020;Lira et al 2020), the significance of PSI in the motor output in PD is demonstrated. However, it is unclear whether this mechanism plays a role as a primary target, or represents, rather, a contributory mechanism to the disturbance in the cortical motor pathways, or represents an insufficient compensatory process to normalize the abnormal motor symptoms.…”
Section: The Significance Of the Loss Of Presynaptic Inhibition For Step Initiation In Parkinsonian Individuals With Freezing Of Gaitmentioning
confidence: 94%
“…In another study (Silva-Batista et al 2017), improvement in the spinal inhibitory mechanisms including PSI was found to be positively associated with the postural instability and quality of life scores in PD subjects and improvement in this function was achieved after resistance training for 12 weeks (Silva-Batista et al 2017). On the other hand, the electrophysiological studies on PD patients undergoing deep brain stimulation (DBS) surgery showed significant improvement in PSI soon after the therapy (Pierantozzi et al 2008;Andrews et al 2020). Combining these study results (Morita et al 2000;Pierantozzi et al 2008;Silva-Batista et al 2017;Andrews et al 2020;Lira et al 2020), the significance of PSI in the motor output in PD is demonstrated.…”
Section: The Significance Of the Loss Of Presynaptic Inhibition For S...mentioning
confidence: 98%
See 1 more Smart Citation
“…A recent study illustrated cortical response features evoked by DBS that are closely related to the hyperdirect pathway through which STN receives input signals from cortical regions [ 101 ]. Another study used intraoperative H-reflex measurement as a potential biomarker for optimal electrode positioning [ 102 ]. Some closed-loop systems could also take multi-modal signals such as acceleration and heart rate as biomarkers [ 103 ].…”
Section: Closed-loop Deep Brain–machine Interfacementioning
confidence: 99%